Complementary role of transcriptomic endotyping and protein-based biomarkers for risk stratification in sepsis-associated acute kidney injury - Tavris, Bengi S.; Morath, Christian; Rupp, Christoph; Szudarek, Roman; Uhle, Florian; Sweeney, Timothy E.; Liesenfeld, Oliver; Fiedler-Kalenka, Mascha; Dubler, Simon; Zeier, Martin; Schmitt, Felix; Weigand, Markus A.; et al. (Critical care, 2025)
Sepsis-associated acute kidney injury (SA-AKI) is a prevalent and severe complication in critically ill patients. However, diagnostic and therapeutic advancements have been hindered by the biological heterogeneity underlying the disease. Both transcriptomic endotyping and biomarker profiling have been proposed individually to identify molecular subtypes of sepsis and may enhance risk stratification. This study aimed to evaluate the utility of combining transcriptomic endotyping with protein-based biomarkers for improving risk stratification in SA-AKI.
Gesehen am 10.11.2025